The Effect of School Climate on Bullying Behavior in Boarding School Students - Annisa Oktaviani; Tarmidi Dadeh; Raras Sutatminingsih (MULTIPLE: Journal of Global and Multidisciplinary, 2024)
This study ains to explore the effect of school climate on bullying behavior in boarding school students, especially those in Medan city. This study uses quantitative methods with the sampling with the sampling technique is total sampling type convinence sampling with the conditions set, namely boarding school students ranging from grade VII junior high school/ MTs to grade XII high school with a total sample of 412 people. The research instrument used a 52-item likert scale test. Validity and reliability tests using the RASCH Winstep Model. The data analysis method used was simple linier regression analysis. The results showed that there was an influence between school climate and bullying behavior in boarding school students, the higher (positive) the school climate, the lower the bullying behavior in the boarding school. There are 6 dimensions of school climate used in this study, namely the dimensions of security, academic, community, institusional environment, educational orientation and culture. In the results of the first and second hypothesis tests, the dimensions that are not significant to bullying behavior are the community dimension and educational orientation because they have a significance value greater than 0.005 (p < 0.005).